Wierność Bogu w diasporze i wśród prześladowań według Księgi Daniela - Parchem, Marek (Verbum Vitae, 2007)
The intention of the Book of Daniel in its historical setting is to exhort and console the faithful Jews in the face of persecution. The content of the exhortation is complete fidelity to God, even at the risk of death. The context of fidelity, however, is different in the two parts of the Book of Daniel. In the tales (Dan 1-6), the context is the service of the Gentile kings. Fidelity to God is shown by the observance o f the peculiar Jewish laws: Daniel 's refusal to eat the king's food (Dan 1), the three Jewish youths do not worship the golden statue (Dan 3), Daniel prays to God three times a day (Dan 6). In the visions (Dan 7-12), the context is confrontation with pagan power. The faithful Jews are persecuted by Antiochus Epiphanes. The maśkilim, "the wise", are to lay down their lives. The death of the martyrs, however, is not in vain. They are the ones who are purified. In Dn 10-12 the specific hope is offered which involves the resurrection ofthe dead. The salvation of the faithful Jews involves their resurrection and exaltation in an afterlife. The risen maśkilim, "the wise", are associated with the angels. The faithful community will share the power of the heavenly holy ones and the wise teachers shine with them in eternal life.